Ameloblastoma with distinctive granular cell pattern - Ana Maria Hoyos Cadavid; Tathyane Harumi Nakajima Teshima; Clóvis Antônio Lopes Pinto; Cláudia Malheiros Coutinho Camillo; Silvia Vanessa Lourenço (University of São Paulo, 2018)
Ameloblastoma with granular cell pattern (AGC) is classified as an unusual histological subtype of solid/multicystic ameloblastoma, characterized by granular changes in stellate-like cells located within the inner portion of the epithelial follicles. Studies have revealed that lysosomal overload causes cytoplasmic granularity; however, the mechanism involved remains poorly understood. Here we report on eight cases of granular cell ameloblastoma, in the posterior region of the mandible. The age of the patients included in this case series ranged from 35 -64 years old and 87.5% of cases occurred in non-Caucasians, with a slight gender predilection for men (62.5%). There was no evidence of recurrence, and the majority of the cases were treated with surgical resection (87.5%). All tumors displayed histopathological features consistent with the diagnosis of ameloblastoma with granular cell pattern.